Books and Written Culture of the Islamic World : Studies Presented to Claude Gilliot on the Occasion of his 75th Birthday = Islamicae litterae scripta : Claudio Gilliot septuagesimum quintum diem natalem celebranti dicata - Rippin, Andrew, 1950-2016; Tottoli, Roberto; Gilliot, Claude (Islamic history and civilization ;, 2015)
An international group of twenty-one friends and colleagues join together to explore authors, genres and traditions of the Muslim world reflecting and honouring the contribution of Claude Gilliot to Islamic studies.